The Implementation of Performance-Based Assessment Technique to Assess Students’ Analysing Skill in English Learning - umniyyatul makmuroh; Hendi Pratama (English Education Journal, 2022)
Performance-based assessment (PBA) offers teachers to figure out students’ authentic language proficiency and encourages students to think critically. The students implemented what they have got in the teaching and learning process in real ways. Moreover, this technique is purposed to help teachers in improving students’ higher-order thinking skill. The first higher-order thinking skills (HOTS) to be achieved among all is analysing skill. Since some studies found that this skill is less assessed. Therefore, this study aims at explaining the implementation of Performance-Based Assessment to assess students’ analysing skill in learning English. Employing qualitative research design, an English teacher who was teaching ninth-grade students at SMPN 2 Semarang and fulfilled the study requirements was selected to be the subject of the study. Data were gathered using classroom observation, document analysis, and interview. The result showed that the teacher applied process-oriented assessment in the implementation of performance-based assessment to assess students’ analysing skill in English learning. Some probing questions were delivered during the going time of learning activities which could trigger students to think critically about the answers at that time. The teacher guided the students in a depth discussion about the learning materials. Most importantly, the questions used to conduct the assessment were WH questions which require HOTS. To sum up, the implementation of PBA to assess students’ analysing skill was done through probing questions. This result is significantly found as a reference in conducting analysing skill assessment.